Novel Hsv Colour Space based Threshold Method for Vegetation Extraction and its Performance on Landsat TM Images - Maarir, Abdelkrim; Benyoucef, Abdelhalim; Bouikhalene, Belaid (International Journal of Engineering and Technology, 2018)
This paper deals with a novel proposed vegetation extraction method applied in multi spectral satellite images (Landsat TM). This proposed method essentially consists of three steps: image enhancement using histogram equalisation, image transformation to new colour model called HSV (Hue, Saturation, and Value) and thresholding application on Hue and Saturation components.Â  For post-processing a hybrid filter median has been used to improve the results and remove isolated pixels. The proposed method is applied to three different scenes of Beni Mellal region in Morocco. The obtained results are compared with two other thresholding methods. Pixels identified as vegetation have an average sensitivity value of 95.88% and an accuracy value of 93.02%.Â Â